2019
DOI: 10.1002/chem.201903054
|View full text |Cite
|
Sign up to set email alerts
|

Carbocatalytic Oxidative Dehydrogenative Couplings of (Hetero)Aryls by Oxidized Multi‐Walled Carbon Nanotubes in Liquid Phase

Abstract: HNO 3 -oxidized carbon nanotubes catalyze oxidative dehydrogenative (ODH) carbon-carbon bond formation between electron-rich (hetero)aryls with O 2 as a terminal oxidant. The recyclable carbocatalytic method provides ac onvenient and an operationally easy synthetic protocol for accessing various benzofused homodimers, biaryls, triphenylenes, and related benzofused heteroaryls that are highly useful frameworks for material chemistry applications.C arbonyls/quinones are the catalytically active site of the carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…In many reported carbocatalysed C−C bond forming reactions the net reaction, i.e., oxidative dehydrogenative (ODH) conversion, has been reported to proceed via acid catalysed, Friedel–Crafts (FC) type mechanism [2] . Furthermore, we [3a,b] and others [4] have demonstrated that carbocatalytic aryl–aryl couplings can proceed through a SET‐based process as well [3a] . We concluded in our recent experimental—computational study that in carbocatalysis both mechanisms can operate depending on the substrate and used catalyst [3b] .…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…In many reported carbocatalysed C−C bond forming reactions the net reaction, i.e., oxidative dehydrogenative (ODH) conversion, has been reported to proceed via acid catalysed, Friedel–Crafts (FC) type mechanism [2] . Furthermore, we [3a,b] and others [4] have demonstrated that carbocatalytic aryl–aryl couplings can proceed through a SET‐based process as well [3a] . We concluded in our recent experimental—computational study that in carbocatalysis both mechanisms can operate depending on the substrate and used catalyst [3b] .…”
Section: Introductionsupporting
confidence: 52%
“…Furthermore, we [3a,b] and others [4] have demonstrated that carbocatalytic aryl–aryl couplings can proceed through a SET‐based process as well [3a] . We concluded in our recent experimental—computational study that in carbocatalysis both mechanisms can operate depending on the substrate and used catalyst [3b] . The reaction mechanisms, however, cannot always be easily distinguished.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations